Critical Discourse The Epistemology of Muhammad Syahrur's Ijtihad - Asep Suraya Maulana; Imam Yahya (Jurnal Hukum Islam, 2020)
Syahrur's offer toward the sceptical-literalist and modernist-secularist attitudes of the Islamic community is, returning to Inzal (al-Qur'an), God's revelation that delivered to the Prophet. This qualitative study, to analyze the epistemology of Syahrur's ijtihad. The results show Syahrur's thinking about epistemology originates from material nature that is beyond human existence. Syahrur in interpreting the ahkam verses still agreed to maintain the purity of the teachings of the Qur'an, which shalah likulli zaman wa makan. According to Syahrur, the truth was based on three pillars, i.e: revelation, reason, and reality. The combination of the 122 Critical Discourse The Epistemology of ......121- 140. (Asep Suraya Maulana) Vol 18 No 1, Juni 2020 ISSN 1829-7382 (Print) 2502-7719 (Online) three resulted in new and modern Islamic legal knowledge. Syahrur's offer, on the theory of scientific historicity, linguistic hermeneutics and Marxist dialectics, shows an attempt to deconstruct science that has been patented in the application of Islamic law. The difference from the concept of classical ijtihad ushul fiqh with the concept of ijtihad Syahrur, i.e: 1) places ijtihad in a vital position for modern Islamic law; 2) ijtihad only at the stage of justifying or forbidding something; 3) requires scientific achievements and modern knowledge systems; 4) allows to ijtihad all legal texts, even though the ulama see as qath'i; and 5) can be done individually